Analisis Efektivitas Bahasa Promosi pada Konten Affiliate Marketing di Tiktok - Hanum aliffia Nuhayah; Ana Putri Nastiti (CV. ITTC INDONESIA, 2026)
The development of digital technology has changed marketing strategies through TikTok platforms that take advantage of short videos as promotional media. This study aims to describe the characteristics of promotional language in affiliate marketing content in TikTok, analyze its effectiveness based on AFA (Attention, Interest, Desire, Action) models, and identify the most dominant linguistic elements used. Research uses a qualitative descriptive method with data obtained through documentation studies on TikTok's video content transcripts, semiterstruktur interview with affiliates, literature study, and scale-based Likert questionnaire to active TikTok users. The results show that promoted language used tends to be persuasive, communicative, follow trends, and take advantage of personal testimonials to build emotional closeness. Hook's sentence at the beginning of the video proved to be effective in attracting audience attention, while the element scarcity, social proof, and call to action (CTA) became the dominant strategy in increasing purchase interest. This finding confirms the importance of effective use of promotional language in supporting the success of affiliate marketing in the digital era.